2019
DOI: 10.1177/2325967119852625
|View full text |Cite
|
Sign up to set email alerts
|

Lower Back Injuries in National Collegiate Athletic Association Football Players: A 5-Season Epidemiological Study

Abstract: Background: Low back injuries are common in collegiate football players and can frequently lead to persistent pain, reinjuries, and time lost from participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Use of the NCAA-ISP has been previously well-described in the literature and will be briefly reviewed. 1 , 3 , 5 , 7 , 9 , 14 , 17 , 22 24 The NCAA-ISP utilizes a voluntary convenience sample of NCAA programs over a 5-year period. Consequently, there is variability in the number of programs participating in the data set each year.…”
Section: Methodsmentioning
confidence: 99%
“…Use of the NCAA-ISP has been previously well-described in the literature and will be briefly reviewed. 1 , 3 , 5 , 7 , 9 , 14 , 17 , 22 24 The NCAA-ISP utilizes a voluntary convenience sample of NCAA programs over a 5-year period. Consequently, there is variability in the number of programs participating in the data set each year.…”
Section: Methodsmentioning
confidence: 99%
“…4,5,7,9,15,21,22 It has been used previously to report on all LSIs in the NCAA over the same time period but has not been used to look at LSIs specifically in male and female basketball athletes. 17 The NCAA ISP is a prospectively gathered injury surveillance program managed by the Datalys Center for Sports Injury Research and Prevention, an independent nonprofit research organization. This study was found to be institutional review board exempt and approved by the research review board of the NCAA.…”
Section: Methodsmentioning
confidence: 99%
“…Weights for all data were further adjusted to correct for underreporting, accounting for the estimated 88.3% capture rate of all time-loss medical care injury events with the NCAA ISP previously reported in the literature. 17 The weighting varied based on sport, exposure type, division played, and calendar year. There was no uniform weight, and each case was weighted based on these contextual factors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations